Effectiveness of community forest user groups (CFUGs) in responding to the 2015 earthquakes and COVID-19 in Nepal. (December 2020) - Gentle, Popular; Maraseni, Tek N.; Paudel, Dinesh; Dahal, Ganga R.; Kanel, Tara; Pathak, Bharati
Abstract: Natural disasters and pandemics are evolving as major global threats that are posing an enormous challenge to socio-economic and environmental wellbeing. Using a real time analysis of the impressive role played by Community Forest User Groups (CFUGs) in Nepal in responding to the 2015 earthquakes (Earthquake-15) and COVID-19, this paper explores the scopes, capacities, institutional strengths and attributes required for community-based institutions such as CFUGs to become effective in managing and responding natural or other disasters. Our findings suggest that being an autonomous and well-recognized community based institution with trusted social capital (trust, connectedness, norms and network) for collective action together with its scope and mandate to democratically manage and mobilize its physical, financial, natural and human assets, CFUGs have become the most effective institution to provide immediate support to disaster affected communities. While most of other agencies including non-governmental organizations spend a lot of time exploring avenues for immediate response to the disasters, CFUGs have immediate access and infrastructure to support millions of people in rural areas. We argue that this contribution needs to be recognized, and CFUGs can provide a valuable institutional framework for the preparedness, response and recovery from disasters and to build resilience in the future.